2013
DOI: 10.1002/app.39553
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun nanofibers from a multihole spinneret with uniform electric field

Abstract: This study presents a multihole spinneret with a metal flat electrode to obtain uniform electric field and meet a high production requirement. We demonstrate that the multihole spinneret produces finer fiber diameters and more concentrated fiber mat compared to the conventional multineedle electrospinnig system. This study focuses on the effect of the electric field distribution on the spinning process and the resultant nanofibers. The three-dimensional electric field simulation results show that the multihole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 21 publications
(26 reference statements)
0
29
0
Order By: Relevance
“…E‐spinning from flat electrode with holes was first reported by Zhou et al in 2009 . Up to now, spinnerets with 1, 3, 4, and 7 holes have been studied. Figure a shows the schematic of multihole experimental setup.…”
Section: Needleless E‐spinning From Stationary Spinneretsmentioning
confidence: 99%
See 3 more Smart Citations
“…E‐spinning from flat electrode with holes was first reported by Zhou et al in 2009 . Up to now, spinnerets with 1, 3, 4, and 7 holes have been studied. Figure a shows the schematic of multihole experimental setup.…”
Section: Needleless E‐spinning From Stationary Spinneretsmentioning
confidence: 99%
“…Not all the stationary spinnerets are suitable for the upward e‐spinning. The spinnerets like flat electrode with holes, tube with linear holes, and conical wire coil, always take the form of downward e‐spinning with the fiber collector right below the spinnerets. Figure lists the stationary spinnerets for downward e‐spinning.…”
Section: Needleless E‐spinning From Stationary Spinneretsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the confined feeding method can produce fibers of special structures, such as core‐shell fibers. Our previous work developed a multihole system with a flat spinneret to scale up the productivity of electrospun nanofibers. We found that this multihole system created a more uniform electric field than the conventional multineedle system.…”
Section: Introductionmentioning
confidence: 99%